Association between work empowerment and interprofessional collaboration among health care professionals working in cancer care settings - Karukivi Johanna; Leino-Kilpi Helena; Kuokkanen Liisa; Kuusisto Hannele; Rautava Päivi; Seppänen Laura; Sulosaari Virpi; Stolt Minna (Taylor & Francis, 2022)
This study aimed to analyze work-related empowerment and interprofessional collaboration and to identify possible associations among healthcare professionals working in cancer care settings. A cross-sectional survey design was employed in this study. Healthcare professionals (n = 175) in one Finnish Cancer Center participating in the care of patients with cancer at least on a monthly basis took part in the study. The data were collected with three instruments: Interprofessional Collaboration and Leadership, Performance of an Empowered Personnel (PEN), and Work-related Empowerment Promoting Factors (WEP). The data were analyzed with descriptive statistics, Pearson and Spearman's correlation coefficients and multivariate analysis using generalized liner models. Healthcare professionals rated their work empowerment as rather high. Performance of an Empowered Personnel (PEN) was perceived as high (mean 4.08, SD 0.47). Promoting factors for Work Empowerment (WEP) were also assessed as high (mean 3.98, SD 0.61). Interprofessional collaboration in the cancer care setting was perceived as moderate (mean 2.94, SD 0.36). Managerial position explained work empowerment based on multivariate analysis. Work empowerment and interprofessional collaboration had a strong correlation. The results can be used in the leadership and management of interprofessional collaboration and in developing new structures to support health professionals' work empowerment. In the future, work empowerment needs to be promoted by constructing solutions and practices that support interprofessional collaboration and thus improve the quality of cancer care.